IPM-FFS Institutionalization In Nepal: A Case Study - Tiwari, Kul Prasad (Journal of Agriculture and Environment, 2013)
FFS is a form of adult education based on the philosophy of experiential learning method aimed at building farmers’ expertise and capacity of analysis, critical thinking and decision-making. The objective of this paper is to assess the institutionalization status of IPM-FFS at the local level. The study is a case study and qualitative in nature. The research was conducted in Kathmandu and Tanahun districts. Hundred farmers from ten FFS, five in each of the district, were interviewed with semi-structured questionnaire. The result showed a seventy-five percent majority of FFS-graduates not having understanding and capacity of conducting experimental learning session in their own initiative. Additionally a majority of sixty percent did not use the knowledge learnt from the FFS learning session. Nevertheless, majority of the graduates acquired a lot of awareness about harmful effects of pesticides to human health, animal and environment. Likewise, eighty percent of the IPM-FFS groups did not repeat learning activities at the local level. Their majority did not share learnt skill to the non-participant farmers for its horizontal dissemination, and have a sense of ownership that empowered them to sustain the process at local level. All exhibited that IPM-FFS approach has not been institutionalized adequately for environment friendly promotion of cultivation. The Journal of Agriculture and Environment Vol:13, Jun.2012, Page 20-26 DOI: http://dx.doi.org/10.3126/aej.v13i0.7583